2001
DOI: 10.1007/s003300100825
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intraocular foreign bodies by helical-CT multiplanar imaging

Abstract: The aim of this study was to examine the effectiveness of helical CT in the assessment of intraocular foreign bodies, evaluating two protocols with different collimation. We performed helical-CT studies in 30 patients. Fifteen patients were examined with 1.5-mm collimation and the other 15 patients with 3.0-mm collimation. All other imaging parameters were identical in both protocols. Multiplanar images were reconstructed. The examinations were reviewed for presence, localization and size of intraocular foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
(21 reference statements)
0
8
0
1
Order By: Relevance
“…Computed tomography is accepted as the imaging modality of choice in detecting and localizing metallic IOFBs, 8,[17][18][19][22][23][24][25] and may even serve in evaluating their size and composition. 21 However, our review of the literature revealed no systematic evaluation of the assessment of nonmetallic IOFBs.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography is accepted as the imaging modality of choice in detecting and localizing metallic IOFBs, 8,[17][18][19][22][23][24][25] and may even serve in evaluating their size and composition. 21 However, our review of the literature revealed no systematic evaluation of the assessment of nonmetallic IOFBs.…”
Section: Discussionmentioning
confidence: 99%
“…B-scan ultrasonography is frequently ordered in this setting as a first line imaging study but has a suboptimal sensitivity for echo lucent foreign bodies and can contribute to an erroneous diagnostic impression 5–8. Orbital computed tomography (CT) scan offers relatively high sensitivity for IOFBs, as has been reported by multiple investigators 5,911. However, the majority of evidence in favor of CT as the imaging modality of choice for detection of IOFB comes from reports of metallic or otherwise radio-opaque (glass or stone) foreign bodies.…”
Section: Discussionmentioning
confidence: 98%
“…18 Such eyes may also have an unusual initial presentation, which may potentially delay IOFB identification. 19 Computed tomography is the procedure of choice for metallic IOFBs, 6,[8][9][10][11][12]15,16,[20][21][22][23] but MRI has been shown to be superior to CT in the identification of nonmetallic IOFBs. 17,24 Ultrasonography may identify nonmetallic IOFBs, but it does not allow recognition of IOFB composition and has been shown to be unable to discern between metallic and nonmetallic IOFBs.…”
Section: Discussionmentioning
confidence: 99%